Implementasi Program Sembako dan E-Warong Kube Dalam Jejaring Kebijakan - Rahmawati, Aulia; Ratnawati, Nanik; Ardiansyah, Muhammad; Wiradi, Rinaldo; Fazardo, Rewind Tri (e-JKPP, 2024)
This research aims to see how the implementation of non-cash basic food programmes and cash basic food programmes within the framework of policy networks. In addition, it also looks at the existence and existence of e-warong kube in the distribution of basic food programmes. The research method used is a qualitative method with data collection techniques of documentation studies, interviews and observations. The findings of this research are that the non-cash basic food programme is more optimal based on the seven dimensions in the policy network framework. In addition, e-warong kube is an empowerment target of the non-cash basic food program which is a major program benefit for the community, especially in terms of socio-economics. Whereas the cash grocery programme does not have an empowerment target.